2021
DOI: 10.2147/jir.s298307
|View full text |Cite
|
Sign up to set email alerts
|

Complement Profiles in Patients with Amyotrophic Lateral Sclerosis: A Prospective Observational Cohort Study

Abstract: Background The complement system has been suggested to be involved in the pathophysiology of amyotrophic lateral sclerosis (ALS), a progressive motor neuron disease. In the present study, we compared levels of selected complement markers to clinical outcome in ALS patients. Methods This observational, explorative cohort study included 92 ALS patients, 61 neurological controls (NCs) admitted for suspected aneurysmal subarachnoid haemorrhage, and 96 neurologically healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Specifically, ALS patients who had higher levels of FIBB in their plasma exhibited longer survival periods, a finding consistent across various potential influencing factors like age, gender, respiratory issues, or functional ability [ 40 ]. C9 is among the proteins engaged in the complement system, serving as a defense mechanism of the body against pathogens [ 41 ]. Karasu et al observed a cytotoxic effect on oligodendrocytes following complement activation, leading to the formation of C9 and subsequent release of EVs rich in membrane attack complex (MAC) from their surface [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, ALS patients who had higher levels of FIBB in their plasma exhibited longer survival periods, a finding consistent across various potential influencing factors like age, gender, respiratory issues, or functional ability [ 40 ]. C9 is among the proteins engaged in the complement system, serving as a defense mechanism of the body against pathogens [ 41 ]. Karasu et al observed a cytotoxic effect on oligodendrocytes following complement activation, leading to the formation of C9 and subsequent release of EVs rich in membrane attack complex (MAC) from their surface [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggest that elevated PRG-4 levels in serum and EVs may serve as a potential biomarker for ALS progression and cognitive impairment. Moreover, the increase in PRG-4+ EVs seen in ALS patients with normal cognitive function may have significant therapeutic potential for treating several other conditions in addition to ALS, comprising traumatic brain injury [ 41 ]. This suggests a potential role for PRG-4+ EVs in promoting recovery and long-term cognitive resilience in various neurological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Other acute phase proteins such as C-reactive protein and CD14 have been detected as elevated in MND sera, and increased levels of these are reported to be associated with disease progression and mortality rate (40). In addition to the aforementioned acute phase proteins, several components of the complement system including C3 (41), C4 (42), and C5a/C5b-9 (43) have been reported to be higher in the whole blood, serum or plasma of ALS cases to controls in previous studies. As such, it may be of value in the future to investigate local accumulation of SAA as a biomarker for disease progression and as a representation of the overall inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some of the early components of this cascade play a beneficial role in synapse elimination during the development of the nervous system, although excessive complement-mediated synaptic pruning in the adult or injured brain may be detrimental in multiple neurogenerative disorders (Schartz and Tenner, 2020 ). A correlation between ALS and the complement system has been frequently described (Carpanini et al, 2019 ; Kjældgaard et al, 2021 ), but a connection to APOE still remains elusive.…”
Section: Discussionmentioning
confidence: 99%